Variable amplitude very high cycle fatigue of 17-4PH steel with a stepwise S-N curve. (January 2021) - Schönbauer, Bernd M.; Fitzka, Michael; Karr, Ulrike; Mayer, Herwig
Highlights: Constant and variable amplitude loading of 17-4PH steel deliver stepwise S-N curves. Transition stress amplitudes separate surface HCF and internal VHCF failures. Transition stresses for CA and VA loading are similar (for both tested load ratios) Separate damage accumulation calculation for surface and interior failure is required. Omission of stress amplitudes lower than 60% of maximum stress in VA tests is allowed. Abstract: High and very high cycle fatigue (VHCF) tests were performed with 17-4PH stainless steel under constant amplitude (CA) and variable amplitude (VA) loading at load ratios of −1 and 0.05. Stepwise (duplex) S-N curves were determined with failure from surface inclusions above the transition stress amplitude, σtr, and from the interior below σtr . Similar σtr for CA and VA loading were found. VA failure occurred at Miner damage sums between 0.1 and 0.9 (surface failure) and 0.2 and 2.2 (internal failure). Omission of stress amplitudes less than 60% of the maximum amplitude is allowable for VA studies in the VHCF regime.